Mysticism and reality in Aboriginal myth: evolution and dynamism in Australian Aboriginal religion. Issue 3 (2nd July 2020) - Hiscock, Peter
ABSTRACT: Religious stories of Australian Aboriginal people, myths, were not stable and long lasting; they were often short-lived and frequently changed. High rates of turnover in narrative content allowed them to incorporate accurate reference to short-lived resources, but was a significant obstacle to the preservation of a story over long periods. Evidence for relatively high rates of religious change challenges us to explain the mechanisms for persistent evolution of religious narrative. This paper proposes an evolutionary model consisting of three elements: (i) creation of novel narratives by recombination of a pool of themes, characters, personalities, and actions, based on the ambiguous and polysemic understanding of dreams and existing myths; (ii) selection or modification of narratives in response to group/audience reactions, leading to some being attached to rites and popularized, (iii) development of regional differences because of the place-attachment of events and characters in stories. Evolutionary change was driven by competition between individual men or alliances of men of high standing who claimed rights to new mythic and ritual domains. Aboriginal myths were therefore not fixed in time, in conservative social systems, but were rapidly changing as individuals and groups renegotiated power relationships and world views.